THE NORWEGIAN CABIN IN CHRISTIAN VALEUR’S "STEFFEN TAR SIN DEL AV ANSVARET" - BOZÎNTAN, Georgiana (Studia Universitatis Babeș-Bolyai Philologia, 2023)
The Norwegian Cabin in Christian Valeur’s Steffen tar sin del av ansvaret. The purpose of this article is to provide an analysis of the representation of the hytte or the Norwegian cabin in Christian Valeur’s 2009 novel Steffen tar sin del av ansvaret (“Steffen Takes His Share of the Responsibility”). Discussing the topos of the hytte, I seek to show how the novel offers a commentary on the Norwegian cabin tradition in the context of the climate crisis in particular and, more generally, on the paradoxical ideas of closeness to nature through consumerism. Drawing on Ellen Rees’s study about cabins in Norwegian literature (2014) and understanding this locus as a heterotopia (Foucault 1986), I discuss how the cabin ironically loses its value of being an “environmentally friendly” form of dwelling, and therefore cannot accomplish its potential role as a heterotopia of compensation. On the other hand, the cabin becomes a place of refuge and self-reflection for the narrator and therefore functions as a heterotopia of crisis. Finally, I suggest we can read the novel in relation to the hyttebok (“cabin book”) conventions, underlining the satirical and subversive nature of the novel towards ecological attitudes in Norwegian society. In this way, I aim to propose a new interpretation of the novel as a work of climate fiction. REZUMAT. Cabana norvegiană în Steffen tar sin del av ansvaret de Christian Valeur. Scopul acestui articol este de a oferi o analiză a reprezentării cabanei norvegiene (hytte) în romanul lui Christian Valeur, Steffen tar sin del av ansvaret („Steffen își asumă responsabilitatea”, 2009). Discutând toposul cabanei, îmi propun să arăt cum romanul aduce un comentariu asupra tradiției cabanei norvegiene în contextul crizei climatice în particular și, în mod general, asupra ideii paradoxale de apropiere față de natură prin consumerism. Având la bază studiul lui Ellen Rees (2014) despre cabanele din literatura norvegiană și înțelegând acest spațiu ca o heterotopie (Foucault 1986), îmi propun să discut cum, în mod ironic, cabana reprezentată în roman își pierde calitatea de formă de locuire „prietenoasă cu mediul” și astfel nu își poate îndeplini rolul potențial de heterotopie de compensație. Pe de altă parte, cabana devine un loc de refugiu și reflexie asupra sinelui pentru personajul-narator, în acest fel funcționând ca heterotopie de criză. În cele din urmă, sugerez că putem citi romanul în raport cu convențiile jurnalului de cabană (hyttebok), punând în evidență caracterul satiric și subversiv al romanului la adresa atitudinilor ecologice din societatea norvegiană. În felul acesta, îmi propun să ofer o nouă interpretare a romanului citit ca ficțiune climatică. Cuvinte-cheie: cabana norvegiană, heterotopie, Christian Valeur, hyttebok, ficțiune climatică. Article history: Received 3 August 2023; Revised 16 November 2023; Accepted 28 November 2023; Available online 20 December 2023; Available print 31 December 2023.